Low pathogenic avian influenza H9N2: world-wide distribution. Issue 1 (1st March 2016) - Al-Garib, S.; Agha, A.; Al-Mesilaty, L.
Abstract : Low pathogenic avian influenza virus (LPAI) subtype H9N2 in poultry has occurred in many countries since the mid-1990s. Outbreaks due to H9N2 have occurred in Korea, Germany, Italy, Ireland, South Africa and the USA. Most recently, H9N2 infections have been reported in several Asian countries, the Middle East and Africa, causing widespread outbreaks in commercial chickens. In these countries, vaccine has been distributed with the aim of controlling the disease. However, H9N2 infections have become endemic in commercial poultry in a significant number of countries. This review is aimed to shed light on the current situation of the LPAI world-wide.